2004
DOI: 10.1103/physrevlett.93.206102
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Structure of Defects in GaN:Mg Grown with Ga Polarity

Abstract: Electron microscope phase images, produced by direct reconstruction of the scattered electron wave from a focal series of high-resolution images, were used to determine the nature of defects formed in GaN:Mg crystals. We studied bulk crystals grown from dilute solutions of atomic nitrogen in liquid gallium at high pressure and thin films grown by the MOCVD method. All the crystals were grown with Ga-polarity. In both types of samples the majority of defects were three dimensional Mg-rich hexagonal pyramids wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 21 publications
(14 reference statements)
1
23
1
Order By: Relevance
“…vs. V "Mott-Schottky" plots) is indicative of the net charge type (donor or acceptor) beneath the surface inversion/accumulation layer [10,11]. This "turnover" occurs at lower applied bias shown to produce donors and reduce the free hole concentration; this result has been attributed to the formation of compensating defect complexes (such as Mg-V N ) [32,33] and pyramidal inversion domains [34,35]. TEM studies of Mg-doped InN, InGaN, and GaN have shown that high levels of Mg result in large densities of planar extended defects, which could also be contributing to the n-type conductivity of overdoped films [36][37][38][39].…”
Section: Electrical and Thermoelectric Measurements A Resultsmentioning
confidence: 99%
“…vs. V "Mott-Schottky" plots) is indicative of the net charge type (donor or acceptor) beneath the surface inversion/accumulation layer [10,11]. This "turnover" occurs at lower applied bias shown to produce donors and reduce the free hole concentration; this result has been attributed to the formation of compensating defect complexes (such as Mg-V N ) [32,33] and pyramidal inversion domains [34,35]. TEM studies of Mg-doped InN, InGaN, and GaN have shown that high levels of Mg result in large densities of planar extended defects, which could also be contributing to the n-type conductivity of overdoped films [36][37][38][39].…”
Section: Electrical and Thermoelectric Measurements A Resultsmentioning
confidence: 99%
“…1,3 According to energy dispersive x-ray spectroscopy and electron energy loss spectroscopy, Mg is incorporated into the top and side facets of these defects. 1,5 The experimental observation that the Mg concentration of 2 Â 10 19 cm À3 , at which pyramidal inversion domains start to form, coincides with the concentration beyond which the free carrier concentration drops led several authors 1,2,6 to conclude that incorporation of Mg in form of Mg 3 N 2 into these defects could explain this drop. As an alternative explanation for the reduced free carrier concentration, compensation of the Mg acceptor by, e.g., nitrogen vacancies (V N ) has been put forward.…”
Section: Pyramidal Inversion Domain Boundaries Revisitedmentioning
confidence: 96%
“…These defects have been studied in the literature and different models were suggested to explain their nature, all of them comprise an enrichment of Mg in the boundary or inside the PDs. Hansen et al [1] stated that the PDs are antibixbyite (Mg 3 N 2 ) precipitates, whereas Liliental-Weber et al [2][3][4][5] observed cavities inside PDs and assert that in the PDs the boundaries are decorated by Mg and covered by GaN of reversed polarity. Vennéguès et al [6] studied Mg doped bulk GaN grown by high-pressure, high-temperature method exhibiting rather large PDs with basal plane diameters of ∼100 nm.…”
Section: Introductionmentioning
confidence: 99%